Topical Diltiazem versus Topical Sucralfate and Lignocaine in the Treatment of Chronic Fissure in Ano: A Prospective Randomized Control Trial - Vinoth Sundaresan; Vinothkumar Sadayappan; R Kannan Rajendiran; T Tirou Aroul (Journal of Surgical Specialties and Rural Practice)
Background: Chronic anal fissure is the most prevalent anorectal disorder, characterized by linear or oval ulcers in the anal canal’s squamous epithelium. Although lateral sphincterotomy stands as the gold standard for treatment, chemical sphincterotomy with calcium channel blockers, nitrates, and botulinum toxins is favored in the initial stages to avoid surgical side effects. Aim and Objectives: The goal is to assess the efficacy of topical diltiazem in treating chronic fissure in ano, particularly its impact on pain, bleeding, discharge, recurrence rates, and healing compared to the lignocaine–sucralfate combination. Materials and Methods: A prospective, randomized controlled study was conducted at Mahatma Gandhi Medical College and Research Institute, Puducherry, from October 2014 to April 2016, involving 100 cases. Subjects were divided into two groups: Group A received topical 2% diltiazem and Group B was treated with 2% lignocaine and 7% sucralfate. Both groups followed a regimen including a high-fiber diet, sitz baths, and laxatives, with follow-ups at 2, 4, 6 weeks, and 6 months to evaluate treatment outcomes. Results: Significant improvements were noted in Group A, with pain reduction from a mean of 6.48 to 0.48 by the 6th week. Both groups saw enhanced healing rates and reductions in symptoms, with Group A exhibiting a lower recurrence rate, indicating the superior efficacy of 2% diltiazem. Conclusion: Topical 2% diltiazem is more effective in treating chronic anal fissure than the combination of 2% lidocaine gel and 7% sucralfate, offering better pain management, healing rates, and lower recurrence, making it a preferred treatment option.